Design of Hydroxyxanthone Derivatives as Breast Cancer Inhibitors: A QSAR Modeling, Molecular Docking, Molecular Dynamics, MM-PBSA and ADMET Prediction - Fatmasari, Nela; Hermawan, Faris; Jumina, Jumina; Kurniawan, Yehezkiel Steven; Pranowo, Harno Dwi; Puspitasari, Anita Dwi; Hastuti, Lathifah Puji; Marlina, Lala Adetia; Putra, Nicky Rahmana (Journal of Multidisciplinary Applied Natural Science, 2025)
A comprehensive QSAR analysis, in conjunction with molecular docking, molecular dynamics simulations, MM-PBSA binding energy estimations, and ADMET profiling, was conducted to facilitate the development of novel anticancer agents based on hydroxyxanthone derivatives. Molecular and electronic descriptors were calculated using the DFT method with the 3-21G basis set. The best QSAR model identified several descriptors that significantly influence anticancer activity, including the atomic charges at positions C1, C3, C4a, and C7, as well as the highest occupied molecular orbital (HOMO), surface area (SA), molecular volume (VOL), and molecular weight (MW). This model was used to design novel hydroxyxanthone derivatives (X27 to X47). The docking result showed that compounds 7-bromo-3-hydroxy-1-(methylamino)-9H-xanthen-9-one (X43), 6-hydroxy-8-(methylamino)-9-oxo-9H-xanthene-2-carbonitrile (X44), and 3-hydroxy-7-mercapto-1-(methylamino)-9H-xanthen-9-one (X45) had stronger binding energy values than gefitinib as a native ligand. Gefitinib had a binding energy of -6.84 kcal/mol, while those compounds had values of -6.92, -7.12, and -6.92 kcal/mol, respectively. In a molecular dynamics simulation of 100 ns, compounds X43, X44, and X45 exhibited stability comparable to that of gefitinib against the EGFR protein. Additionally, the binding energy MM-PBSA of compound X43 was the lowest (-29.18 kcal/mol), followed by X44 (-27.11 kcal/mol), gefitinib (-26.06 kcal/mol), and X45 (-25.21 kcal/mol). Furthermore, these compounds met Lipinski's rule parameters and the minimal standard parameters in terms of ADMET characteristics, as predicted by physicochemical properties. In conclusion, compounds X43, X44, and X45 are potential anticancer agents for MDA-MB-231 breast cancer cells.